If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-6+2=5x+9
We move all terms to the left:
5x-6+2-(5x+9)=0
We add all the numbers together, and all the variables
5x-(5x+9)-4=0
We get rid of parentheses
5x-5x-9-4=0
We add all the numbers together, and all the variables
-13!=0
There is no solution for this equation
| 5x-4+2=5x+9 | | 5x-4+2=5x+11 | | 5x-4+2=5x+10 | | X(32-2x)(24-2x)=1 | | 4x-2=14x-83 | | -6+4x=4x+4 | | -2(x)-9=-19 | | 17x-11=68 | | -2(0.25x+2)=10 | | 7x-5+2=8x+8 | | 7x-5+2=9x+8 | | x+20+2x+10+x-10=180 | | 17x48=x | | (x+12)(x)=960 | | (x+1)(x+2)(x+3)(x+6)=3x² | | 5x+3=2x-14 | | 8x-30=4x+50 | | X+18;x=12 | | -x+5=10x+2 | | 8-3x=7x-10 | | 2x•x=72 | | 2x+2(2x-4)=24 | | 3y+5=15+5 | | 16x+28x=2 | | 34x-7=34 | | 34x+7=34 | | 5x+7=12x+15 | | 40x^2-13x-1=0 | | 1.21÷(x+0.3)=1.1 | | 5x+7=12x+3 | | 2/k=6/11 | | 17y+3-12y-3=4 |